A natural history note on the Pseudoneoponera ant-mimicking behaviour of Naddia sp. (Staphylinidae: Staphylininae: Staphylinini: Staphylinina), from Kalyani University campus, Kalyani, Nadia, West Bengal, India. - Bhattacharjee, Banani; Chakrovorty, Arnob; Háva, Jiří; Samadder, Asmita (Zootaxa, 2024)
A unique ant-mimicking behaviour has been observed in the rove beetle genus Naddia sp. (Coleoptera: Staphylinidae: Staphylininae: Staphylinini: Staphylinina) from the campus of the University of Kalyani, Kalyani, Nadia, West Bengal, India. The individual has been observed to undergo imperfect Batesian mimicry by mimicking ants of the genus Pseudoneoponera (Hymenoptera: Formicidae: Ponerinae: Ponerini).